KEWAJIBAN NOTIFIKASI PENGAMBILALIHAN ASET PERUSAHAAN DALAM PERSPEKTIF HUKUM PERSAINGAN USAHA [Mandatory Notification for Company's Asset Acquisition in the Perspective of Competition Law] - Anna Maria Tri Anggraini (Law Review, 2021)
The Indonesian business competition supervisory agency, KPPU, issued KPPU Regulation No. 3/2019 which regulates the control system for merger, consolidation, and acquisition of company shares (P3S). This regulation was established to address the development of supervisory issues, including the expansion of the term expropriation, which includes the takeover of assets. Although it is not explicitly regulated in Law no. 5/1999 and PP No. 57/2010, the facts on the ground show that the enactment of the KPPU Regulation has been complied with by business actors within a period of more than a year since its stipulation. This article presents two research issues regarding the reasons behind KPPU's issuance of the regulation, and the legal implications of the enactment of new regulations for business actors and practitioners. This article is the result of normative research supported by secondary data in the form of legal regulations in the field of competition, comparisons with several countries, examples of the takeover of Uber assets by Grab, and also using interviews with two KPPU sources. The data was then analyzed qualitatively and concluded by using a deductive method. The conclusion drawn is that the purpose of KPPU in drafting the regulation is to prevent monopolistic practices and unfair business competition, by conducting benchmarking which results in the finding that the takeover of assets can also potentially give a chance to a concentrated market and anti-competitive behavior. The formation of the regulation also has juridical and sociological implications, namely fulfilling the legal aspect and being obeyed by business actors by notifying the takeover of shares and assets.Bahasa Indonesia Abstrak: Lembaga pengawas persaingan, KPPU, menerbitkan Perkom No. 3/2019 yang mengatur tentang sistem pengendalian atas penggabungan, peleburan dan pengambilalihan saham perusahaan (P3S). Peraturan ini dibentuk untuk menjawab perkembangan isu pengawasan, antara lain perluasan istilah pengambilalihan, yang meliputi pula pengambilalihan aset. Meskipun tidak diatur secara eksplisit dalam UU No. 5/1999 maupun PP No. 57/2010, fakta di lapangan menunjukkan bahwa pengundangan Peraturan KPPU tersebut telah dipatuhi oleh pelaku usaha dalam kurun waktu lebih dari setahun sejak ditetapkannya. Artikel ini mengemukakan dua masalah penelitian tentang hal-hal yang melatarbelakangi KPPU menerbitkan peraturan tersebut, dan implikasi hukum pemberlakukan peraturan baru terhadap pelaku usaha maupun praktisi. Artikel ini merupakan hasil penelitian normatif yang didukung data sekunder berupa peraturan hukum di bidang persaingan, perbandingan dengan beberapa negara, contoh pengambilalihan aset Uber oleh Grab, dan juga menggunakan wawancara dengan dua narasumber KPPU. Data tersebut kemudian dianalisis secara kualitatif dan menyimpulkannya dengan metode deduktif. Kesimpulan yang dihasilkan adalah bahwa maksud KPPU menyusun peraturan tersebut adalah melakukan pencegahan terjadinya praktik monopoli dan persaingan usaha tidak sehat, dengan melakukan benchmarking yang menghasilkan temuan, bahwa pengambilalihan aset juga dapat berpotensi melahirkan pasar yang terkonsentrasi dan perilaku antipersaingan. Pembentukan peraturan tersebut juga berimplikasi secara yuridis maupun sosiologis, yakni memenuhi aspek legalitas dan dipatuhi pelaku usaha dengan melakukan notifikasi pengambilalihan saham maupun aset.